Bildung – nicht Standardisierung (mathematica didactica, 2006)
This article reminds us of our pedagogical obligation to grant every student a chance for his personal education. It does so facing the newest wave of technical controlling running over our educational system supported by normative standardization which is being enforced by continuous evaluation. In order for genuine education to happen, the student has to be challenged by significant contents within suitable contexts. This situation, especially, requires didactics of mathematics far beyond narrow-minded research projects.